Bioactivity, hydrophilic, lipophilic and volatile compounds in pulps and skins of Opuntia macrorhiza and Opuntia microdasys fruits. (May 2019) - Chahdoura, Hassiba; Barreira, João C.M.; Barros, Lillian; Dias, Maria Inês; Calhelha, Ricardo C.; Flamini, Guido; Soković, Marina; Achour, Lotfi; Ferreira, Isabel C.F.R.
Abstract: Opuntia genus includes several species able to grow in arid regions and known for producing delicate fruits, which are far from being thoroughly characterized. Herein, fruits from O. macrorhiza and O. microdasys were divided in skins and pulps (without including seeds) and studied for chemical composition, individual phytochemicals and bioactivity. The major volatiles were camphor and ethyl acetate, while citric acid was the main organic acid. The fatty acids detected in highest percentages were linoleic acid (skins) and lauric acid (pulps); α-tocopherol was the major isoform of vitamin E. Quercetin-3- O -rutinoside and quercetin- O -(deoxyhexoside-rutinoside) were the main phenolics in fruit skins of O. macrorhiza and O. microdasys (respectively), similarly to piscidic acid in O. macrorhiza pulp ( O. microdasys pulp showed no quantifiable compounds). Betanin and isobetanin were the major betalains. All samples were antioxidant (particularly O. macrorhiza ), but antimicrobial activity was only detected in skins. Cytotoxicity was low in all cases. Overall, these fruits proved to be potential new ingredients for food or pharmaceutical related applications, adding value to these natural species able to grow in arid environments. Highlights: Significant differences were found among skins and pulps of each species. Main volatiles, lipophilic compounds, phenolic compounds and betalains were identified. Opuntia spp. skins and pulps were antioxidant and antimicrobial, and reveal low cytotoxicity. The profiled compounds indicate potential applications of these underused ruderal species.